The competence of the United Nations Security Council to consider the Lockerbie case - Mohammad Yonis Al-Sayegh (الرافدین للحقوق, 2011)
After the Libya extradite the suspects in the Lockerbie case to the Scottish court after the families of the victims compensated very appropriate compensation as well as compensation of Pan Am and Other parties concerned . The Scottish courts have spoken to judge Abdel Basset al-Megrahi in jail for 20 years through the ruling, issued on 31/1/2001 Vooda prison Barlini city of Glasgow in Scotland. Have sacrificed the United States and embarked Makintha Balenaiq media when he decided to Scottish Justice Minister Kenny Mkasil release of Megrahi in 20/8/2009 is suffering from prostate Sultan at a late stage and it may take three months after the third item on the basis of Scottish law, a prison and the prosecution of criminals in 1993, which gives the Minister of Justice the authority to pardon prisoners on medicalparole. This law has been applied over the past years where he was Minister of Justice released 26 people. The USA and Britain have considered that the release of Megrahi and then venture betweeni( ) BP and the Libyan government, which is BP's pressure on the British government for the release of al-Megrahi for protecting a deal to explore for oil off the coast of Libya, valued at 900 million dollars and this action angers families victims. Where is respect for the laws of other countries and where the principle of non-interference Blackmail American States is established and maintained and its violations of international law began to worsen and escalate it represents the international law and overseeing the implementation by States of their laws and human rights and other Sawa tools for this intervention, which began by adapting the principles of the Charter in trends and in accordance with the views consider American Constrained in August 1990 when the Iraqi army to Kuwait as well as in the Lockerbie case. USA, where she founded new concepts in reading the texts of the Charter and the rules and mechanisms used to deal with them, they decide that this incident is a threat to international peace and security or not, which decide that the resolution issued under Chapter VII or under Chapter VI. The Security Council has passed three resolutions availing Lockerbie first in Chapter VI and the other two under Chapter VII, bypassing the other United Nations bodies and international court of justice is not indifferent to adapt the incident with the rules of international law, international conventions, which represents a Massarha. .